A PROFIT AND LOSS ACCOUNT ANALYSIS ON CORRECTIVE MAINTENANCE SYSTEM - Nita Marikena; Yuli setiawannie; Susilawati Susilawati (Sean Institute, 2023)
Machinery and equipment is one of the production factors that affect the smooth production process. With a maintenance system can help so that the machine or equipment can work in accordance with its function. Electrical manufacturing companies currently do not have a scheduled maintenance system so that if the machine is damaged then there is no repair. Repairs made after damage occurs can incur maintenance costs which result in the cessation of the production process. Based on these problems, the purpose of this study is to determine the company's profit/loss if it applies corrective maintenance with profit and loss account calculations. Based on the results of calculations using the profit and loss account method, it is obtained that the company has a net profit that increases every year after implementing the corrective maintenance system, with the profit value in the 5 years being 2018 amounting to IDR 1,922,000, 2019 amounting to IDR 2,722,440, 2020 amounting to IDR 3,529,000, 2021 amounting to IDR 3,686,640, and 2022 amounting to IDR 3,850,400.